Knowledge of results after relatively good trials enhances self-efficacy and motor learning - Saemi, E.; Porter, J. M.; Ghotbi-Varzaneh, A.; Zarghami, M.; Maleki, F. (Psychology of Sport and Exercise, 2012)
Objectives: This study sought to determine whether learners` self-efficacy and motor learning was affected by the type of feedback they were provided. Method: Participants (N = 24, M age = 19.51 years, SD = 1.08) were randomly assigned into one of two groups: knowledge of result after good versus poor trials. The task included throwing a tennis ball with the non-dominate hand to a target while wearing vision distorting goggles. Participants completed the Self-Efficacy Scale (Bandura, 2006) before performing each block of 6 trials. A retention test without knowledge of results was conducted 24 h after the practice phase. Results: The results demonstrated that learners` motor learning was increased by providing knowledge of results after good rather than poor trials. Furthermore, the Self-Efficacy Scale results revealed that learners` self-efficacy was enhanced by positive feedback. Conclusions: The current findings indicate that positive feedback impacts learner`s self-efficacy, and enhances performance and motor learning.